From sunset to sunrise - Devendra Maheshwari; Nimrita Nagdev; Madhavi Ramanatha Pillai; Shivam Gupta (Kerala Journal of Ophthalmology)
A 38-year-old male patient presented with blunt trauma in right eye (RE), 3 days back. On examination of RE, the best corrected visual acuity was light perception and intra-ocular pressure (IOP) was 42 mmHg by applanation. Anterior segment examination showed dislocated lens in anterior vitreous cavity. Ultrasound sonography showed no evidence of vitreous hemorrhage or retinal detachment. Maximum medical anti-glaucoma therapy was started. After 1 week, due to uncontrolled IOP and dislocated lens, pars plana vitrectomy with lensectomy with scleral fixated intra-ocular lens implantation was done. On 2-week follow-up, IOP was 18 mmHg on monotherapy, with stable lens and retina.